DIGITAL MARKETING MODEL OF INDOMIE ICE CREAM’S VIRAL MARKETING - Daniel Susilo; Lu Hui Chen (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
Industry progressed significantly day by day, especially in digital era. Indonesia doesn’t escape this loop especially with their cultured habit and the way they consume trusted product. This time Indomie shines again as the product looked by everyone due to their flashy new product named Indomie Ice Cream. Indomie Ice Cream and the Ice Cream’s sweetened clashed each other, yet people in Twitter still so eager to buy it and taste it themselves. With SWOT analysis, this research shows how Indomie makes an advanced impact through opportunities even though the type of product isn’t dominantly loved by people like regular Indomie or regular ice cream.